Penerapan Asam Lemak Hidroksamat dalam Industri Farmasi dan Kosmetik - Muhsinun, Muhsinun; Yanuar, Emsal (Journal of Science and Technology: Alpha, 2025)
This study aims to explore the application of hydroxamic fatty acids in the pharmaceutical and cosmetic industries, with a focus on their biological activities, product formulations, and compound stability in practical applications. Biological activity assays demonstrated that hydroxamic fatty acids exhibit significant antimicrobial effects against Escherichia coli and Staphylococcus aureus, as well as effective anti-inflammatory activity by reducing the production of pro-inflammatory cytokines in RAW 264.7 cells. Furthermore, anticancer tests on human breast cancer cells (MCF-7) showed that these compounds can inhibit cancer cell proliferation. In terms of product formulation, hydroxamic fatty acids were found to be stable in cosmetic products (facial serums and hair masks) and pharmaceutical products (topical ointments), with results indicating improvements in skin elasticity and hair quality, along with a reduction in inflammation symptoms in patients. However, a major challenge in the application of hydroxamic fatty acids lies in their complex synthesis process, which requires hazardous chemicals, thereby increasing production costs and impacting environmental sustainability. Therefore, further research is needed to develop more efficient and environmentally friendly synthesis methods. Overall, the findings of this study suggest that hydroxamic fatty acids hold significant potential for development as effective and safe active ingredients in the pharmaceutical and cosmetic industries.